If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -4) = -1(4x + 9) Reorder the terms: (-4 + 8x) = -1(4x + 9) Remove parenthesis around (-4 + 8x) -4 + 8x = -1(4x + 9) Reorder the terms: -4 + 8x = -1(9 + 4x) -4 + 8x = (9 * -1 + 4x * -1) -4 + 8x = (-9 + -4x) Solving -4 + 8x = -9 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -4 + 8x + 4x = -9 + -4x + 4x Combine like terms: 8x + 4x = 12x -4 + 12x = -9 + -4x + 4x Combine like terms: -4x + 4x = 0 -4 + 12x = -9 + 0 -4 + 12x = -9 Add '4' to each side of the equation. -4 + 4 + 12x = -9 + 4 Combine like terms: -4 + 4 = 0 0 + 12x = -9 + 4 12x = -9 + 4 Combine like terms: -9 + 4 = -5 12x = -5 Divide each side by '12'. x = -0.4166666667 Simplifying x = -0.4166666667
| 3z-8-z+2=0 | | -2.5+3.2= | | (x+40)+(2x-5)+(3x-17)=180 | | -6x^2-26x+20=0 | | 6k+6(1-7k)=39-3k | | x+(x-35)+(x-46)+.5x=360 | | x^2+8x=-13 | | 7y+3x-7+5x-2y=0 | | 2x^2+3x=-8 | | 5(x+3)=3(1-x) | | r(s)=n | | 15x^2y^2+7xy-2=0 | | -3(2n+1)+6=2n | | 4*x+y=9 | | 9x^5y^7= | | 5x+15=3-3x | | k^2=6k-5 | | 5x-8=-8+3x | | 8-2a=7 | | 14x^2y^2+5xy-24=0 | | 1x+18+1x-20=90 | | 7(2x+4+y)= | | 5y^3+34y^2-7y=0 | | 0.04(y-1)+0.12y=0.06y-0.03(20) | | 15/46= | | .5x=3.5 | | 3-6(x+3)=3 | | 2x^2+26x+80= | | 2x^3+5x^2-42x=0 | | -4x-9y-2x+12y= | | 3x-70+x+50=180 | | -5(6-x)+6=10-7(x+2) |